Age, Growth and Mortality Rates of Symphodus tinca (Osteichthyes: Labridae) in Izmir Bay (NE Aegean Sea) - Okan Akyol; Gülnur Metin (Aquatic Sciences and Engineering)
A total of 373 Symphodus tinca specimens were obtained from small-scale fisheries in January 2017 - December 2018 off Urla coasts (Izmir Bay), north-eastern Aegean Sea. The length and weight distribution of all S. tinca specimens ranged from 7.8 to 24.5 cm TL (mean: 14.4 ± 0.12) and from 6.6 to 209.3 g (mean: 43.2 ± 1.30), respectively. The female – male ratio was 1:0.41. The weight-length relationship parameters (a, b, r2 ) were calculated to be 0.0175, 2.9023 and 0.9629, respectively. The age of S. tinca was determined to be between 0 and V years. The von Bertalanffy growth parameters were L∞ = 39.06 ± 23.57 cm, K = 0.14 ± 0.14, and t0 = -1.77 ± 0.77. In addition, the Von Bertalanffy Growth Formula for length is given by the following equation: Lt = 39.06 [1 – e -0.14 (t + 1.77)]. Thus, the growth performance (Φ`) was estimated as 2.32. The values of mortality and exploitation rates of S. tinca are 1.015 (Z), 0.380 (M), 0.635 (F) and 0.626 (E), respectively. These results indicate that stocks of S. tinca in the Bay of Izmir are overexploited.